The Problem of the Grey Area in e-Trade in Poland - Anna Ćwiąkała-Małys; Iwona Piotrowska (Barometr Regionalny)
E-trade is one of the most buoyant ways of selling goods and services in Poland. All activity in this field is very attractive not only for marketing companies but also for auditing and fiscal authorities. The results of analyses show that on-line trading is threatened however by the existence of a grey area. This refers, in particular, to non-registered business activity and avoidance of taxation on trade income. The aim of this article is to show the main risks of e-trade in Poland which may influence the state budget, and some legislative solutions which have an effect of a gradual limitation of fiscal fraud in e-trade. Source material constituted results of analyses that were conducted by the Polish Central Statistical Office, independent research units and studies by specialized marketing companies on the scope of the grey area in e-commerce in Poland. A comparative analysis of the size of the grey area shows that regardless of the difference in results of its measurements, the grey area is a common phenomenon. Accessibility of new technologies (computerization of enterprises and households and Internet accessibility) favors the development of e-commerce and the existence of a grey area within it.